Effectiveness of Physics Mobile Learning in Generation Z: A Literature Review - Sisda Ferlianti; Ridwan Efendi; Selly Feranie (Jurnal Ilmiah Profesi Pendidikan, 2023)
Today, the using of mobile learning tools are much needed. One of those mobile learning is physics mobile learning. This study aims to analyze the effectiveness of using physics mobile learning in physics learning in generation z students. The analysis was carried out on journal articles that have implemented physics mobile learning. The research subjects consisted of twenty five journal articles selected from the Scopus Index database, Web of Science (WOS), Google Scholar, or ERIC from 2012 to 2022. The data have already been analyzed related to improved orientation aspects, and research methods. The results of data analysis indicate that the use of mobile physical learning can have a positive impact on enhancing the different abilities of students, such as HOTS abilities, diagrammatic and argumentative representation skills, and students' conceptual understanding. According to our analysis of the development of physics mobile learning, students consider these apps to be an interesting and useful addition to traditional teaching, as they allow them to easily access multimedia resources and learn almost anywhere and anytime. This means that more research is needed to develop mobile learning physics in other physics concepts used and improved orientation aspects.